2008
DOI: 10.1007/s00277-008-0661-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in sickle β-thalassemia

Abstract: Cardiovascular involvement is a leading cause of mortality and morbidity in patients with inherited hemoglobinopathies, but it has not been adequately assessed in sickle β-thalassemia. We evaluated 115 sickle β-thalassemia patients, aged 34±14 years, along with 50 healthy controls, by resting echocardiography. Patients with systolic left ventricular (LV) dysfunction or severe pulmonary hypertension (PHT) also underwent left and right cardiac catheterization and cardiac magnetic resonance imaging (CMR). Left an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 40 publications
3
31
0
2
Order By: Relevance
“…12 In sickle-thalassemia, a compound heterozygous state with 1 thalassemia and 1 sickle allele, PH has been observed with a rather lower frequency and a definitely lesser severity. [15][16][17] It should be stressed that with the exception of thalassemia intermedia, in which PH was confirmed by right-sided heart catheterization in 2 of the previously cited trials, 8,9 the vast majority of studies in thalassemia and sickle cell disease used echocardiography as a screening tool, and therefore, the reported prevalence may be overestimated by at least some of those trials.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…12 In sickle-thalassemia, a compound heterozygous state with 1 thalassemia and 1 sickle allele, PH has been observed with a rather lower frequency and a definitely lesser severity. [15][16][17] It should be stressed that with the exception of thalassemia intermedia, in which PH was confirmed by right-sided heart catheterization in 2 of the previously cited trials, 8,9 the vast majority of studies in thalassemia and sickle cell disease used echocardiography as a screening tool, and therefore, the reported prevalence may be overestimated by at least some of those trials.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…23 In this context, other investigators have found a poor correlation between PH and markers of hemolysis in patients with sickle-thalassemia, in whom a lower hemolytic rate may be present. 16,17 It appears that the relative severity of hemolysis in different hemolytic conditions may determine the degree of its contribution to the development of PH. Regardless, the interaction between hemolysis and nitric oxide depletion is currently beyond doubt because it is supported by the bulk of evidence derived from both experimental and clinical studies.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Iron overload not only lead to left heart dysfunction, it also causes liver disease contributing further to the development of PH due to liver cirrhosis. [6424344] In short, the pathobiology of PH in hemolytic disorders is a rainbow of many colors. Mechanisms like NO depletion, dysregulated arginine metabolism, oxidative stress and hypercoagulable state result in pulmonary vasoconstriction, endothelial proliferation and hyperplasia, and in situ thrombi.…”
Section: Pathophysiologymentioning
confidence: 99%